2020
DOI: 10.1016/j.drugpo.2019.102619
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of injecting among people who inject drugs: A systematic review and meta-analysis

Abstract: Frequency of injecting among people who inject drugs: a systematic review and meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…For overdose, confounders included: methadone use, biological sex, time since onset of injecting, excessive weekly alcohol consumption, whether prescribed naloxone in the past year, whether homeless in past six months (Darke & Hall, 2003;Handanagic, Bozicevic, Sekerija, Rutherford, & Begovac, 2019;O'Halloran et al, 2017;Riley et al, 2016). For injecting frequency, confounders included methadone use, biological sex, time since onset of injecting, whether homeless in past six months (Colledge et al, 2020;Fortier et al, 2020;Van Beek et al, 2001). For main body site of injection, confounders included: methadone use, biological sex, injected cocaine in past six months, time since onset of injecting, injecting frequency, whether homeless in past six months (Darke et al, 2001;Karimi et al, 2014;Rhodes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For overdose, confounders included: methadone use, biological sex, time since onset of injecting, excessive weekly alcohol consumption, whether prescribed naloxone in the past year, whether homeless in past six months (Darke & Hall, 2003;Handanagic, Bozicevic, Sekerija, Rutherford, & Begovac, 2019;O'Halloran et al, 2017;Riley et al, 2016). For injecting frequency, confounders included methadone use, biological sex, time since onset of injecting, whether homeless in past six months (Colledge et al, 2020;Fortier et al, 2020;Van Beek et al, 2001). For main body site of injection, confounders included: methadone use, biological sex, injected cocaine in past six months, time since onset of injecting, injecting frequency, whether homeless in past six months (Darke et al, 2001;Karimi et al, 2014;Rhodes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Study-level variables included year of data collection, sample size, method of recruitment (e.g. NSP centres, peer referrals, and surveys), sex, age (median, mean, and/or range), length of time injecting (in years), frequency of injecting (extracted by the categories defined in the original study and then grouped as daily or more and less than daily injecting; for more detail see 21 ), incarceration history (past 12 months and lifetime), homelessness or unstable housing (within the past year), current engagement in opioid agonist therapy (OAT), and opioids as main drug injected.…”
Section: Table 1 About Herementioning
confidence: 99%
“…After reviewing changes in RR over time, we did not identify any events meeting our threshold for an acute respiratory depression nor were there any self reports of an opioid overdose (i.e., no reports of receiving naloxone). It is possible that this may be related to a pattern of lower-frequency, low-dose injection that is associated with a protective effect (Colledge et al, 2020) since our sample reported injecting an average of 1.4 bag of fentanyl per event (data not shown), despite an average of roughly 5 fentanyl injections per day. In qualitative exit interviews, participants indicated low volume use was a conscious act of harm reduction and reported using just enough to ons, along with the short duration of the study we did not capture any events meeting our definition of overdose and were unable to cross-reference RR with actigraphy data.…”
Section: Discussionmentioning
confidence: 88%